Management of Teacher Competency Development and Training in Improving Learning Quality - Hafizi; Iim Wasliman; Hanafiah; Faiz Karim Fatkhullah (Journal of Education Reseach and Evaluation, 2022)
Management of teacher competency development and training in improving learning quality still has constraints on planning, organizing, implementing, and evaluating. This study aimed to describe the management of teacher competency development and training in improving learning quality. This qualitative study used case-study and descriptive methods. Data were collected using observations, interviews, and documentation then reduced, presented, and concluded. Based on the results, the management of teacher competency development and training in improving learning quality has been running to improve teacher competence making them have the structure, concept and scientific mindset to excel students through high learning quality even though it is not optimal due to constraints on the number of teachers, mismatches with qualifications, oriented to assignment scheduling, low HR quality, and low mastery of technology so that the proposed solution is to train teachers to have good competence, teach according to their own expertise, career development through functional roles based on credit score calculations, motivate teachers to continue study to a higher level, provide opportunities for teachers to participate in training, raise salaries, conduct clinical supervision to all teachers, and assess learning tools owned by teachers.